(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
This article reviews key aspects for defining the South-west epigraphic culture, with the aim of assessing whether it can be attributed to a Palaeo-ethnic group of the Iberian Peninsula. It first examines the evidence that allows the phenomenon to be placed geographically and chronologically, before confronting these data with the accounts of GrecoRoman historians and geographers in search of possible corresponding ethnonyms. The main supports of this script are briefly outlined, alongside reflections on the intentions behind the extant inscriptions. Finally, a new nomenclature for this epigraphic culture is proposed, while questioning the supposed funerary function of most inscribed stelae.